Thermoresponsive Microspheres as Smart Pore Plugs: Self‐Venting Clothing Membranes for Smart Outdoor Textiles. Issue 4 (7th February 2018) - Stucki, Mario; Stöckli, Marco; Stark, Wendelin J.
Abstract: Rapidly changing temperature and precipitation conditions are challenging for clothing textiles when required to keep us warm under harsh weather. A smart functional outdoor membrane based on thermoresponsive poly( N ‐isopropylacrylamide) (PNIPAM) microspheres embedded into a polyurethane matrix is developed. Selective dissolution of two‐particle composite precursors affords porous membranes with PNIPAM microspheres located within the pore walls. Adjusting the mean size of the thermoresponsive microplug permits us to switch membrane breathability depending on outdoor temperature. In cold conditions, the textile fabric closes off pores and reduces heat loss, as to keep a person warmer. Under hot conditions, the PNIPAM microplugs open up, and self‐vent the jacket, allowing for high breathability and heat transfer. The resulting smart membranes are tested according to international standards. The principle of phase separation based microplug positioning within pores, and selective opening and closing of pores may enable other smart applications in material sciences, biology, and other consumer products. Abstract : Rapidly changing weather conditions are challenging for clothing when required to keep us warm. A smart functional outdoor membrane based on thermoresponsive PNIPAM microspheres embedded into a polyurethane matrix is developed. In cold conditions, the membrane closes pores and reduces heat loss. Under hot conditions, the pores open up allowing for high breathability and heat transfer.